Effects of Dietary Sweet Orange (Citrus sinensis) Waste on Crude Protein Digestibility and Body Weight of Padjadjaran Rams - Kurnani, Tubagus Benito Achmad; Adriani, Lovita; Hidayat, Ujang; Hernawan, Elvia; Bandiati, Sri (Pakistan Journal of Nutrition, 2017)
Background and Objective: Sweet orange (Citrus sinensis) being an environmental threat and having many dietary beneficial effects, it could be used in the diet of livestock. Therefore, the present study was conducted with the objective to study the effect of dietary inclusion of Citrus sinensis waste on Padjadjaran sheep. Materials and Methods: This study used 20 Padjadjaran rams with average body weight of 30.42±4.50 kg. The rams were divided into 4 treatments of 5 animals. The sweet orange waste was used at the rate of 0% (control group-R0), 12% (R1), 17% (R2) and 22% (R3). The parameters estimated were crude protein digestibility, initial body weight, final body weight, body weight increase and crude protein of feed. Results: The results indicated that the dietary inclusion of sweet orange waste had no significant (p>0.05) effect on the crude protein digestibility of rams when compared with the control group. However, the highest crude protein digestibility (55.26±13.27%) was observed in the group wherein diet of rams was supplemented with 12% sweet orange waste (R2), followed by (53.40±9.04%) the control group. Further, there was no significant (p>0.05) effect on the body weight of rams fed various levels of sweet orange waste when compared with the control group. Highest body weight (0.63±0.94) was found in the control group, followed by (0.59±0.67) R3 group (fed 22% sweet orange waste in the diet). Conclusion: The inclusion of sweet orange waste up to 22% in the diet had no negative effect in terms of crude protein digestibility and body weight increase of Padjadjaran rams.